Developing a theoretical framework of chinese culture of excellence for economic innovations - Da, An; Boo, Ho Voon; Wen, Chiat Lee (UiTM Cawangan Kedah, 2022)
Chinese excellence traditional culture continues to prosper in the times of rapid economic development in recent years. The Chinese culture has been catching up with the Western culture in popularity. Chinese government has always advocated the importance of Chinese culture and advised the Chinese to learn the excellent culture. It is believed that the Chinese culture excellence can bring great economic development and innovations to China. However, there is still a lacking of conceptual understanding of the Chinese culture of excellence and its impact on economic innovations. This paper intends to address that problem. Using the case of universities and colleges in Ningxia Hui Autonomous Region, this paper explores the relationship between Chinese excellent culture and economic innovation. A theoretical framework on how Chinese excellent culture leads to economic innovation is constructed and presented. With the construction of theoretical framework of the Chinese culture, there is a better understanding of how Chinese excellence culture can lead to economic innovation. The understanding is useful for policy makers especially at the universities level to encourage culture excellence training and learning that will lead to economic innovation in the long run.